The national entertainments and games of the kyrgyz people in the late 19th century and early 20th century [pp. 290-295] - Türkmen, Mehmet (INT JOURNAL LIFESCIENCE & PHARMA RESEARCH, 2021)
This study tries to trace the cultural elements that the Kyrgyz people's national entertainments and games played in Kyrgyzstan embodied in the late 19th and early 20th centuries, and to determine their place in social structure and life. Importance: Traditional games performed in the national entertainments also serve as a cultural representation. Symbols, ceremonies and rituals that bring people together not only strengthen bonds between individuals in a society and provide social integration, but also keep the society alive by helping the society to maintain its traditions through sports tradition, and make value judgements and morals take root. Understanding the Kyrgyz people's national entertainments and traditional sports games undoubtedly shed light on other aspects of the social life of the Kyrgyz people and even other Turkestan peoples. Objective: It is aimed to define Kyrgyz national festivals and the traditional games performed in Kyrgyzstan; to define some social-cultural institutions, national and religious elements taking part in the form and intellectual elements of the games held in festival events; to explain important cultural elements that were changed or transformed, lost and about to disappear. Method: Descriptive research and comparison model, which is one of the patterns in the qualitative approach, was used in a chronological framework limited to the late 19th century and early 20th century. Conclusion: Kyrgyz national festivals took part in every stage of their social structure and life such as politics, religion, economy, family and etc. and the traditional games, whose performance in these activities is an ancient tradition, were performed intensively during the period of the study as well. The Kyrgyz people characterized the games as the supplements and protectors of their cultural heritage with the concern of losing their national identity and they were able to ensure the continuity of the traditional bond with these games and managed the continuity of the traditional bond with these games.
Keywords: The Kyrgyz people; National entertainment; National games; Mourning ceremony